(NsOWETSKIJ UGOLOWNYJ PROCESS (B:s (Nu^EBNOE POSOBIE (B/s - (NaLEKSEEW(B, (Nn(B.(Ns(B.s; (NbASTRYKIN(B, (Na(B.(Ni(B.s; (NdAEW(B, (Nw(B.(Ng(B.s; (NaLEKSEEW(B, (NnIKOLAJ sERGEEWI^s; (NlUKA[EWI^(B, (Nw(B.(Nz(B.s ((NlENINGRAD (B:s (NiZD(B-(NWO lgu(B,s, 1989)
(NaLF(B.-(NPREDM(B. (NUKAZ(B.: 451-463s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NuGOLOWNYJ PROCESS(B, (NSOWETSKIJs